Examine the parenting style effect on the academic achievement orientation of secondary school students: The moderating role of digital literacy - Hassan, Mehdi; Malik, Asma Seemi; Sang, Guoyuan; Rizwan, Muhammad; Mushtaque, Iqra; Naveed, Shaheryar (Frontiers in Psychology, 2022)
The purpose of the study was to determine the association between parenting styles (authoritative and permissive) and students’ self-efficacy (LSE), self-regulatory learning (SRL), and academic accomplishment orientation of secondary school students in Punjab, Pakistan. The study also investigated the effect of digital learning as a moderating variable in the relationship between SRL and academic achievement oriented, as well as between learner self-efficacy (LSE) and academic achievement among secondary school students. The study was conducted with (N = 720) secondary school students of Punjab Pakistan. In the current research cross sectional design was used, and multistage sampling was used to draw a sample from the population. The results from the study, it is found that the authoritative parenting style has a weak association with LSE and a strong association with SRL. Permissive parenting styles have low associations with SRL and have a high association with LSE as compared to authoritarian parenting. Furthermore, when compared to students from permissive parenting, secondary students from authoritarian parenting have higher SRL and a higher academic achievement orientation. Results revealed that that digital literacy significantly moderate with LSE to influence the academic achievement orientation, while digital literacy significantly interacts with SRL to highly influence the academic achievement orientation of secondary school students.